The relationship between the command of scientific knowledge and language with high order thinking skills among students - Mohd. Rafi, I. B. (Serials Publications, 2017)
This research aims at studying the level of relationship between the command of scientific knowledge and language with the high order thinking skills among students. A total of 180 Form 2 students from secondary schools in Skudai was engaged as the samples for this study. The method used in this study was a descriptive survey. The instrument used in this research is Test Set. Data obtained were analysed as descriptive analysis. The results showed that students achievements for the three aspects studied: knowledge, scientific language and thinking skills were of moderate level which was pass and made the minimum proficiency level. The results also showed that scientific knowledge and language have positive relation to the high order thinking skills among the students. The correlation value between the knowledge and thinking skills was high that is +0.70. Next, the correlation value was moderate between the scientific knowledge and language at +0.62. For the correlation value was moderate between the scientific language and high order thinking skills, that is +0.53. Based on the results of this study, a few suggestions were submitted to assist the schools to identify their students understanding in science and also on the improvement for future research.